DIGITAL FOOTPRINTS IN CRIME INVESTIGATION - Poselskaya, Lyudmila; Skachko, Anna; Gaevoy, Alexander; Khmelev, Sergey; Medvedeva, Anna (Revista Inclusiones, 2020)
This article studies the modern framework of the digital economy and the characteristic features of crime investigation in terms of the widespread implementation of digital technologies. Recently, there is the emergence of electronic documents and e-signature as new objects that may carry forensic information. Therefore, there is the issue of detection and fixation of digital footprints. We highlight the importance of continuous communication with specialists in Information Technology during the preliminary investigation of crimes committed in the economic sphere.